Challenges of Using Artificial Intelligence (AI) Technologies in Teaching Arabic in Public and Private Schools in the Sultanate of Oman from the Teachers’ Perspective (Journal Of Educational and Psychological Researches, 2025)
The research seeks to reveal the challenges of employing artificial intelligence (AI) technologies in teaching Arabic in public and private sector schools in the Sultanate of Oman from the teachers' perspective, as well as to examine the differences of the research sample in terms of gender, school affiliation, academic qualification, and number of years of experience. The research adopted the descriptive analytical approach. The research sample included 166 male and female teachers from the second cycle of basic education in the Sultanate of Oman. A questionnaire of 39 items distributed over three axes—cognitive and skill challenges, technical challenges, and ethical challenges—was administered to the research sample. The results showed that the challenges of employing artificial intelligence (AI) technologies in teaching Arabic in public and private sector schools in the Sultanate of Oman from the teachers' perspective, in the overall score of the questionnaire, are high. There are no statistically significant differences over challenges of applying artificial intelligence technologies in teaching, gender, school affiliation, academic qualification, and number of years of experience. The researcher suggested providing educational institutions with training programs for teachers on the use of artificial intelligence technologies in teaching and calling for the development of Arabic language curricula by including them in learning activities that require the use of artificial intelligence technologies.